Analisis Karakteristik Superposisi Pada Suara Gamelan Dengan Menggunakan Aplikasi Spectra Plus dan Audacity - Aristyarini Cahyadiningrat; Fara Afida Ramadhani; Fadli Aulia Salim; Ghazy Refindramiqdad Glasieradyaksa; Raditya Martanegara; Khafidh Nur Aziz (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2023)
This research aims to analyze the characteristics of superposition waves in the musical instrument known as "saron" in the gamelan ensemble. In this study, three types of gamelan sarons were used as research instruments: "saron demung," "saron barung," and "saron panerus" or "peking." The sounds produced by these musical instruments were recorded, mixed, and analyzed using Audacity software and Spectra Plus Sound Card Edition. The analysis results conducted with Audacity and Spectra Plus Sound Card Edition revealed the presence of superposition waves that either reinforced each other when they had the same phase and frequency or weakened each other when they had different phases and frequencies. Therefore, this study concludes that audio mixing that falls under constructive or reinforcing superposition of waves is the combination of "saron demung" with "saron demung." On the other hand, audio mixing that falls under the destructive superposition of waves includes the varieties of "saron barung" with "peking," "saron barung 1" with "demung," "saron barung 2" with "peking," and "saron barung 2" with "demung."